Alkaline stress reduces root waving by regulating PIN7 vacuolar transport - Liu, Yu; Mu, Chenglin; Du, Dongdong; Yang, Yi; Li, Lixin; Xuan, Wei; Kircher, Stefan; Palme, Klaus; Li, Xugang; Li, Ruixi (Frontiers in Plant Science, 2022)
Root development and plasticity are assessed via diverse endogenous and environmental cues, including phytohormones, nutrition, and stress. In this study, we observed that roots in model plant Arabidopsis thaliana exhibited waving and oscillating phenotypes under normal conditions but lost this pattern when subjected to alkaline stress. We later showed that alkaline treatment disturbed the auxin gradient in roots and increased auxin signal in columella cells. We further demonstrated that the auxin efflux transporter PIN-FORMED 7 (PIN7) but not PIN3 was translocated to vacuole lumen under alkaline stress. This process is essential for root response to alkaline stress because the pin7 knockout mutants retained the root waving phenotype. Moreover, we provided evidence that the PIN7 vacuolar transport might not depend on the ARF-GEFs but required the proper function of an ESCRT subunit known as FYVE domain protein required for endosomal sorting 1 (FREE1). Induced silencing of FREE1 disrupted the vacuolar transport of PIN7 and reduced sensitivity to alkaline stress, further highlighting the importance of this cellular process. In conclusion, our work reveals a new role of PIN7 in regulating root morphology under alkaline stress.